Communicating employability: the role of communicative competence for Zimbabwean highly skilled migrants in the UK - Madziva, Roda; McGrath, Simon; Thondhlana, Juliet (Springer Verlag, 2014)
Skilled migration is an increasingly important topic for both policy and research internationally. OECD governments in particular are wrestling with tensions between their desire to use skilled migration to be on the winning side in the ‘global war for talent’ and their pandering to and/or attempts to outflank rising xenophobia. One aspect that has received relatively little attention is skilled migration from the African Commonwealth to the UK, a situation in which skilled migrants have relatively high levels of linguistic capital in the language of the host country. We focus here on the case of Zimbabwe. In spite of its popular image as a failed state, Zimbabwe has an exceptionally strong educational tradition and high levels of literacy and fluency in English. Drawing on 20 in-depth interviews of Zimbabwean highly skilled migrants, we explore the specific ways in which the communicative competences of these migrants with high formal levels of English operate in complex ways to shape their employability strategies and outcomes. We offer two main findings: first, that a dichotomy exists between their high level formal linguistic competence and their ability to communicate in less formal interactions, which challenges their employability, at least when they first move to the UK; and second, that they also lack, at least initially, the competence to narrativise their employability in ways that are culturally appropriate in England. Thus, to realise the full potential of their high levels of human capital, they need to learn how to communicate competently in a very different social and occupational milieu. Some have achieved this, but others continue to struggle.